Fibroblast growth factor-2 is a sputum remodeling biomarker of severe asthma. (March 2014) - Bissonnette, Élyse Y.; Madore, Anne-Marie; Chakir, Jamila; Laviolette, Michel; Boulet, Louis-Philippe; Hamid, Qutayba; Bergeron, Céline; Maghni, Karim; Laprise, Catherine
Abstract Objective: Given the large phenotypic diversity of asthma, our aim was to characterize molecular profiles related to asthma severity using selected remodeling biomarkers in induced sputum. Methods: Induced sputum from healthy controls, patients with mild to moderate asthma and severe asthma were collected. Twelve selected biomarkers previously associated to airway remodeling such as connective tissue growth factor (CTGF), fibroblast growth factor (FGF)-2, matrix metalloproteinase (MMP)-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, MMP-12, MMP-13, procollagen type 1 and tissue inhibitor of metalloproteinase (TIMP)-1 were measured in sputum samples using ELISA or Luminex technology. FGF-2 level was also evaluated in bronchial biopsies using immunohistochemistry. Results: Sputum of severe asthma was characterized by reduced percentage of macrophages and increased percentage of neutrophils and eosinophils. FGF-2, MMP-1 and TIMP-1 levels increased with asthma severity. Interestingly, only FGF-2 level inversely correlated with FEV1/FVC ratio. Although percentage of eosinophils correlated with asthma severity, it did not correlate with FGF-2 levels. Increased levels of FGF-2 with asthma severity were confirmed in bronchial biopsies by immunohistochemistry. Conclusions: Level of FGF-2 in induced sputum represents a relevant remodeling biomarker of asthma severity and significantly correlates with pulmonary function. FGF-2 sputum biomarker is proposed to reveal the phenotype of asthma characterized by fixed airflow obstruction.